Risk Factors for Group A Streptococcus Colonization During an Outbreak Among People Experiencing Homelessness in Anchorage, Alaska, 2017. (18th May 2018) - Adebanjo, Tolulope; Mosites, Emily; Van Beneden, Chris A; Onukwube, Jennifer; Blum, Matthew; Harper, Michael; Rudolph, Karen; Frick, Anna; Castrodale, Louisa; McLaughlin, Joseph; Bruce, Michael G; Gounder, Prabhu
Abstract: We identified risk factors for any emm type group A streptococcal (GAS) colonization while investigating an invasive emm 26.3 GAS outbreak among people experiencing homelessness in Alaska. Risk factors included upper extremity skin breakdown, sleeping outdoors, sharing blankets, and infrequent tooth brushing. Our results may help guide control efforts in future outbreaks.